Approaches to securing intellectual property rights for competitive advantage for South African corporations. - Clark, Charl Henning (My University, 2014)
ABSTRACT Corporations fight many battles to match and eventually beat their competitors in the marketplace. The development and usage of intellectual property provides a springboard for competitive advantage, but there are many factors that hamper corporations in order to strategise and benefit fully from their proprietary intellectual property. The objective of this research was to identify these factors and to find out what corporations are doing in order to protect their intellectual property for purposes of competitive advantage. The research was conducted through in-depth semi structured interviews with respondents from corporations who deal with such corporations’ intellectual property on a day to day basis and with respondents from firms of attorneys who specialises in the field of intellectual property law. The findings of the research are that notwithstanding the fact that corporations in general understand the benefits of identifying, documenting and protecting their intellectual property, that there are many factors that prevent these benefits from being capitalised on. In order for corporations to fully reap the competitive advantage benefit from their intellectual property, it is recommended that corporations conduct intellectual property audits, employ dedicated intellectual property custodian(s), build a relationship with a firm of attorneys that understand the corporation’s intellectual property portfolio, ensure active leadership support for intellectual property portfolio management and develop the necessary documentation, policies and procedures that focus on the protection of intellectual property.
MBA 2008
Keywords: Intellectual property